Strategic procurement in construction towards better practice in the management of construction supply chains - Cox, Andrew W. (Thomas Telford, 1998)
This work considers the current nature of the UK construction industry, looking at the limitations of conventional procurement systems and the need for a new approach to procurement in the face of the recession and overseas competition.